Evaluating The Basement Design of Low-Rise Building with Two-Stage Analysis using BIM Integration: Hangar Study Case - Tohho, Given; Sjah, Jessica; Rarasati, Ayomi Dita; Trigunarsyah, Bambang (UI Scholars Hub, 2024)
Building Information Modelling (BIM) has revolutionized the way the construction industry designs, constructs, and manages buildings. Certainly, the utilization of BIM can optimize the usage of materials in a construction project, considering the high level of concrete consumption globally and its significant environmental impact. The implementation of BIM is intended to calculate the volume of concrete and steel material usage in the design process of low-rise buildings with basements, exemplified in this case by a 5-story laboratory hangar with a 1-story basement. The building design is carried out through a two-stage analysis, which involves separating the upper portion from the lower portion of the structure. This analysis procedure is commonly conducted in building design with basements. When designing the lower portion, some practitioners often neglect the lateral soil forces in the global model when designing the column and beam elements, assuming that these forces are sufficiently small and can be accommodated by basement wall reinforcement. In this research, with a shallow basement depth configuration, the study compares the extent of differences in structural dimensions and materials caused by these lateral forces. Significant variations in volume are observed in perimeter columns, primarily due to direct soil loads acting on this area. Additionally, considering the function of these columns as boundary elements for the basement walls, such differences are expected. The application of lateral soil forces on basement walls is determined by the specific basement configuration being designed. This includes assessing whether there are additional walls outside the basement walls, which can be analyzed locally since they are assumed to bear the lateral soil loads occurring. Different analyses yield varying reinforcement and concrete volumes in basement structures, especially between models with and without lateral soil loads, resulting in a 7.73% difference in reinforcement and 4.69% difference in concrete volume.